Science Learning Concepts Calligraphy in Modern Pesantren (Qur'anic Art and Calligraphy at Central Java and Darul Arafah Raya in North Sumatra) - Citra Sukma Ayu; Abdurrahman Abdurrahman (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
The concept of calligraphy learning in two different sites, Pesantren Seni dan Kaligrafi Al-Quran and Pesantren Darul Arafah Raya, each of these pesantren has its own way to develop the art of calligraphy. The purpose of this research is to find a comprehensive understanding of the disparity of learning that exists in Pesantren Seni dan Kaligrafi Al-Qur'an and Pesantren Darul Arafah Raya. This research is a descriptive qualitative approach method. Data collection and analysis were carried out using observation and interview techniques. The results of the study can be understood that: in terms of calligraphy learning at the Al-Quran Art and Calligraphy Boarding School, it is more focused where the learning concept combines pure art and calligraphy, as well as the training program at the Al-Quran Art and Calligraphy Boarding School is divided into three, namely: regular, course, and market, finally for the complementary curriculum itself, namely: entrepreneurship, book studies, recitation and GRC, As for Pesantren Darul Arafah Raya: for calligraphy learning at Pesantren Darul Arafah Raya is divided into two forms, namely: subjects and extracurriculars, even with a relatively limited learning allocation, as well as for calligraphy material, it is not the main subject of learning at this pesantren.